Direct Femtosecond Laser Printing of Silk Fibroin Microstructures - Santos, Moliria V. (2020)
Fabrication of functional silk fibroin microstructures has extensive applications in biotechnology and photonics. Considerable progress has been made based on lithographic methods and self-assembly approaches. However, most methods require chemical modification of silk fibroin, which restricts the functionalities of the designed materials. At the same time, femtosecond laser-induced forward transfer (fs-LIFT) has been explored as a simple and attractive processing tool for microprinting of high-resolution structures. In this paper, we propose the use of LIFT with fs-pulses for creating high-resolution structures of regenerated silk fibroin (SF). Furthermore, upon adding Eu3+/Tb3+ complexes to SF, we have been able to demonstrate the printing by LIFT of luminescent SF structures with a resolution on the order of 2 μm and without material degradation. This approach provides a facile method for printing well-defined two-dimensional (2D) micropatterns of pure and functionalized SF, which can be used in a wide range of optical and biomedical applications.